Influence of lightweight aggregate on the bond properties of concrete with various strength grades - Mo, K.H.; Alengaram, Ubagaram Johnson; Visintin, P.; Goh, S.H.; Jumaat, Mohd Zamin (Elsevier, 2015)
This paper presents the comparison of the bond and mechanical properties of lightweight oil palm shell concrete (OPSC) and normal weight concrete (NWC) with three different strength grades of 25, 35 and 45 MPa. Although the mechanical properties such as splitting tensile strength and modulus of elasticity as well as the performance of drying shrinkage of OPSC were found to be inferior compared to NWC, the bond strength of OPSC was found to be up to 80 higher compared to the corresponding NWC of equivalent cube compressive strength grade. Results also showed that the shape of the bond stress-slip curve for OPSC was similar to conventional NWC. In addition, in this paper, modified bond models based on the CEB-FIP bond model was proposed for both OPSC and NWC which were found to give good prediction of the experimental bond stress-slip curve of the concretes. (c) 2015 Elsevier Ltd. All rights